“I loved before, but now I love even more.” Qualitative study of posttraumatic growth as a consequence of severe COVID-19 experience in Slovak adults - Tencerová, Jana; Halama, Peter; Uhrecký, Branislav (Frontiers in Psychology, 2024)
The results indicate that post-traumatic growth does indeed occur after overcoming the severe form of COVID-19. It suggests that this posttraumatic growth most often occurred through a reassessment of priorities and an appreciation of life itself and loved ones. COVID-19 disease has been one of the most discussed and researched topics for several years, as it dramatically affects everyone's daily life. The qualitative study presented here focuses on health psychology, especially post-traumatic growth after overcoming a severe form of the COVID-19 disease. We worked with adult people who had either been treated in the intensive care unit or had been hospitalized with severe pneumonia. Thematic analysis was used to determine categories and subcategories. The study presented here contributes to knowledge about the COVID-19 experience by mapping a Slovakian sample of adult participants. The results obtained by Thematic analysis help us better understand how people experience the disease, especially those who have overcome a severe form of the disease and thus had a borderline experience when their lives were directly threatened, as well as their overall health.